2021
DOI: 10.21203/rs.3.rs-923659/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of COVID-19 Vaccine Acceptability Among Health Professions Students in Vietnam

Abstract: Background: The COVID-19 vaccine hesitancy or refusal has actually been a threat to global health. In the current situation, health profession students are at risk for SARS-CoV-2 infection during their internship at healthcare facilities. Furthermore, those future healthcare workers will advise people to accept the COVID-19 vaccination. Therefore, the attitude of students towards vaccine acceptance and the predicting factors needs to be elucidated. This study applied the Health Belief Model to determine predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
3
8
0
Order By: Relevance
“…In tandem with reinforcing the benefits of vaccination, it is also important to continue addressing concerns (if any) about the “maleficence” of vaccination to foster favourable risk-benefit evaluations [ 18 , 71 ]. Several studies have shown that vaccine safety is one of the key factors associated with vaccine hesitancy [ 69 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Issues concerning quality control (e.g., rapid development and approval of COVID-19 vaccines) and side effects were among the most commonly cited safety concerns that have contributed towards COVID-19 vaccine hesitancy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tandem with reinforcing the benefits of vaccination, it is also important to continue addressing concerns (if any) about the “maleficence” of vaccination to foster favourable risk-benefit evaluations [ 18 , 71 ]. Several studies have shown that vaccine safety is one of the key factors associated with vaccine hesitancy [ 69 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Issues concerning quality control (e.g., rapid development and approval of COVID-19 vaccines) and side effects were among the most commonly cited safety concerns that have contributed towards COVID-19 vaccine hesitancy [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived benefits was inversely associated with COVID-19 vaccine hesitancy in twelve studies [6,[11][12][13][15][16][17][18]20,22,23]. A positive association between perceived barriers and vaccine hesitancy was reported by twelve studies [6,[11][12][13][15][16][17][18][19][20]22,24]. Perceived susceptibility was negatively correlated with COVID-19 vaccine hesitancy in eight studies [10,12,14,[16][17][18]20,23]; however, Chen et al [11] reported a positive correlation between perceived susceptibility and vaccine hesitancy.…”
Section: Hbm Constructs Associated With Vaccine Hesitancymentioning
confidence: 92%
“…Other HBM components that are inversely related were cues to action in nine studies [6,10,11,16,17,19,21,22,24], perceived severity in six studies [14,16,17,19,23,24], and selfefficacy in one study [11]. Griva et al [13] and Guillon and Kergall [6] found a negative effect of perceived threat (i.e., a combined measure of perceived susceptibility and severity) on vaccine hesitancy.…”
Section: Hbm Constructs Associated With Vaccine Hesitancymentioning
confidence: 99%
See 2 more Smart Citations